Factors Affecting the Quality of Audit in Makassar City Inspectorate - Adinda Tania Savitri (Pustaka Digital Indonesia, 2021)
This study aims to determine the factors that influence audit quality at the Makassar City Inspectorate Office. This study uses quantitative research methods. The data obtained from primary data is through the distribution of questionnaires. Respondents in this study were auditors who worked at the Makassar City Inspectorate Office. The questionnaire was processed using the SPSS ver 26 application. This research is expected to be an input for the Makassar City Inspectorate Apparatus and so that the government can improve as a supervisor and examiner of local governments to create good government. The results of this study indicate that independence and competence have a significant effect on audit quality in the city of Makassar, work experience has no significant effect on audit quality. This shows that the higher the level of independence and competence of the auditor, the better the quality of the audit produced.